(untitled) (Anclajes, 2026)
The approaches gathered here explore contemporary Hispanic and Latin American narratives that challenge conventional forms of memoir writing. The aim, therefore, is to observe how these reinterpretations of the past are developed in the voices of subjects who have been historically subalternised and, therefore, excluded from what is commonly acceptable, possible or valid. In the face of a literary field that favours patriarchal, masculine (and masculinised), bourgeois, urban, heterocentric and westernised discourses, we bring to thefore those that are critical of the institutionalised statu quo by offering peripheral or disruptive views on issues of class, gender, geographical origin, social class or ideology.